The Role of Parental and Community Support in Promoting English Language Learning in Rural Schools: A Qualitative Study - Darma, Virga Putra; Apriani, Reni (Sinergi International Journal of Education, 2024)
This study investigates the role of parental and community support in promoting English language learning (ELL) in rural schools. The study adopts a qualitative approach with two complementary methods: a phenomenological study and a case study. The phenomenological study involves semi-structured interviews with 20 rural students from different grade levels and 10 parents from different socioeconomic backgrounds to understand their lived experiences of ELL and the challenges and benefits they encounter. The case study involves a detailed analysis of one rural school that has implemented a successful ELL program with strong parental and community involvement. The case study uses multiple sources of data, such as observations, documents, and focus group discussions with teachers and community members, to examine the processes and outcomes of the ELL program. The study reveals that parental and community support can have positive effects on students’ ELL outcomes and opportunities, such as motivation, achievement, confidence, exposure, and access. However, the study also identifies some challenges and barriers that limit the potential of parental and community support, such as lack of resources, knowledge, skills, time, and trust. The study also highlights the diversity and variability of parental and community support across different contexts, such as grade levels, socioeconomic backgrounds, ethnic groups, and regions. The study also suggests some implications and recommendations for policy makers, educators, and stakeholders who are interested in enhancing ELL provision and quality in rural schools.